Radial Artery Calcification in Predicting Coronary Calcification and Atherosclerosis Burden - Alexandru Achim; Kornél Kákonyi; Ferenc Nagy; Zoltán Jambrik; Albert Varga; Attila Nemes; Jeffrey Shi Kai Chan; Gabor G. Toth; Zoltán Ruzsa (Cardiology Research and Practice)
Background. Atherosclerosis is a systemic arterial disease with heterogeneous involvement in all vascular beds; however, studies examining the relationship between coronary and radial artery calcification are lacking. The purpose of this study was to assess the relationship between the two sites and the prognostic value of radial artery calcification (RC) for coronary artery disease. Methods. This is a single-center, retrospective cross-sectional study based on Doppler ultrasound of radial artery (RUS) and coronary artery angiography (CAG). We included a total of 202 patients undergoing RUS during distal radial access and CAG at the same procedure, between December 2020 and May 2021, from which 103 were found having RC during RUS (RC group) and 99 without (NRC group). Coronary calcifications were evaluated either by angiography examination (moderate and severe), positive CT (>100 Agatson units), or intracoronary imaging (IVUS, OCT). Results. A significant correlation was observed between radial calcification and coronary calcification variables (67.3% vs. 32.7%, p=0.001). The correlation between risk factors such as age, smoking, chronic kidney disease, and diabetes mellitus was higher while sex did not play a role. The need of PCI and/or CABG was higher in the RC group (60% vs. 44%, p=0.02). RC, therefore, predicts the extent and severity of coronary artery disease. Conclusion. RC may be frequently associated with calcific coronary plaques. These findings highlight the potential beneficial examination of radial arteries whenever CAD is suspected.